MINAT MAHASISWA DALAM BERWIRAUSAHA SAMPAH PLASTIK DITINJAU DARI KEMAMPUAN LITERASI LINGKUNGAN - Pangoloan Soleman Ritonga; Arif Yasthophi; Paijan Rambe (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to see how the influence of environmental literacy on the entrepreneurial interest of UIN Suska Riau students. The method of data collection in this study is a questionnaire with a total sample of 121 students at UIN Suska Riau. Data analysis using SEM Path Analysis 3.0 and SPSS 21. The results of the study showed that there was an influence of environmental literacy on the interest in waste entrepreneurship of UIN Suska Riau students which showed that the value of the path coefficient came from the original sample estimate (beta), which was positive, which was 0.471 which showed that the direction of the relationship between Environmental Literacy and Student Entrepreneurial Interest was positive and had a significant influence on the 2-way test (t table = 1.97) with a T-statistical value of 20.818 which was greater than t table,Â and the value of p value is less than alpha 5% (0.000 < 0.05) which means that environmental literacy has a significant effect on students' interest in entrepreneurship at UIN Suska Riau.